Blast Overpressure Waves Induce Transient Anxiety and Regional Changes in Cerebral Glucose Metabolism and Delayed Hyperarousal in Rats - Awwad, Hibah O.; Gonzalez, Larry P.; Tompkins, Paul; Lerner, Megan; Brackett, Daniel J.; Awasthi, Vibhudutta; Standifer, Kelly M. (Frontiers in Neurology, 2015)
Physiological alterations, anxiety, and cognitive disorders are strongly associated with blast-induced traumatic brain injury (blast TBI), and are common symptoms in service personnel exposed to blasts. Since 2006, 25,000–30,000 new TBI cases are diagnosed annually in U.S. Service members; increasing evidence confirms that primary blast exposure causes diffuse axonal injury and is often accompanied by altered behavioral outcomes. Behavioral and acute metabolic effects resulting from blast to the head in the absence of thoracic contributions from the periphery were examined, following a single blast wave directed to the head of male Sprague-Dawley rats protected by a lead shield over the torso. An 80 psi head blast produced cognitive deficits that were detected in working memory. Blast TBI rats displayed increased anxiety as determined by elevated plus maze at day 9 post-blast compared to sham rats; blast TBI rats spent significantly more time than the sham controls in the closed arms (p < 0.05; n = 8–11). Interestingly, anxiety symptoms were absent at days 22 and 48 post-blast. Instead, blast TBI rats displayed increased rearing behavior at day 48 post-blast compared to sham rats. Blast TBI rats also exhibited suppressed acoustic startle responses, but similar pre-pulse inhibition at day 15 post-blast compared to sham rats. Acute physiological alterations in cerebral glucose metabolism were determined by positron emission tomography 1 and 9 days post-blast using 18F-fluorodeoxyglucose (18F-FDG). Global glucose uptake in blast TBI rat brains increased at day 1 post-blast (p < 0.05; n = 4–6) and returned to sham levels by day 9. Our results indicate a transient increase in cerebral metabolism following a blast injury. Markers for reactive astrogliosis and neuronal damage were noted by immunoblotting motor cortex tissue from day 10 post-blast in blast TBI rats compared to sham controls (p < 0.05; n = 5–6).